The World Wide Web Conference 2019
DOI: 10.1145/3308558.3313638
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Blocked Community Members: Redemption, Recidivism and Departure

Abstract: Community norm violations can impair constructive communication and collaboration online. As a defense mechanism, community moderators often address such transgressions by temporarily blocking the perpetrator. Such actions, however, come with the cost of potentially alienating community members. Given this tradeoff, it is essential to understand to what extent, and in which situations, this common moderation practice is effective in reinforcing community rules.In this work, we introduce a computational framewo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Cheng et al [8]'s social-feedback experiments, mentioned above, demonstrate increased commenting rates after receiving low community evaluations, an observation that supports H-Engagement. However, the temporary-ban study by Chang and Danescu-Niculescu-Mizil [5] on Wikipedia found no significant change in future activity rate.…”
Section: H-engagement: Prior Workmentioning
confidence: 92%
See 2 more Smart Citations
“…Cheng et al [8]'s social-feedback experiments, mentioned above, demonstrate increased commenting rates after receiving low community evaluations, an observation that supports H-Engagement. However, the temporary-ban study by Chang and Danescu-Niculescu-Mizil [5] on Wikipedia found no significant change in future activity rate.…”
Section: H-engagement: Prior Workmentioning
confidence: 92%
“…CMV provides a detailed description of moderation standards and practices through a wiki page that is visible to all users 5 . A comment may be removed by a moderator if it is considered to violate one or more rules, such as by being rude or hostile, not challenging the original post, or violating any Reddit site-wide policy.…”
Section: Comment Removal In CMVmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work of volunteer moderators and moderation mainly focuses on user-governed platforms such as Wikipedia [11,33], and Reddit [9,16,29]. Twitch, as a user-moderated, live-streaming community, is similar in some governance aspects to other online communities such as Reddit, which is a self-reliant community [29], and Facebook Group, which provides multiparty interactions [51].…”
Section: Introductionmentioning
confidence: 99%
“…This sampling decision was similar to that used in other studies to control for the effects of previous experiences when examining longitudinal user behaviour (e.g. Chang & Danescu-Niculescu-Mizil, 2019). This decision was bolstered by past studies which have found that prior postings on a community already strongly predict future postings on the same community (e.g.…”
Section: Summary Of Results By Using the Community Detection Processmentioning
confidence: 95%